Analcite based on ball milling activation of organic acid as well as preparation method and application of analcite
By performing organic acid ball milling activation and hydrothermal treatment on lithium slag, efficient and stable zeolite was successfully prepared, which solved the technical problem of converting lithium slag into zeolite, and achieved the resource utilization of lithium slag and high-temperature sulfur-resistant and arsenic removal effect.
Patent Information
- Application Number
- CN202411395360.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-08
Smart Images

Figure CN119528165A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of treated analcime, in particular to analcime activated by organic acid ball milling and a preparation method and application thereof. Background Art
[0002] Lithium slag is waste residue produced in the process of extracting lithium from ore. It is an industrial silico-aluminous waste residue produced in the process of producing lithium salts such as lithium carbonate after high-temperature calcination of lithium ore. It faces the problems of large stockpiling and difficulty in resource utilization. Analcime is a common feldspar-like mineral belonging to the zeolite family. It has a special structure and properties. It has ion exchange, catalytic properties, thermal stability and acid resistance. It is widely used in building materials, environmental protection, daily light industry, petrochemical industry and other fields. Therefore, converting lithium slag into analcime can not only achieve the treatment of solid waste, but also obtain resource-based products and realize the resource utilization of solid waste.
[0003] The Chinese invention patent application with publication number CN117643861A (the applicant's previous case) discloses a sulfur-resistant and high-temperature-resistant gaseous arsenic adsorption material and its preparation method and application. Although the gaseous arsenic adsorption material is prepared by mechanical ball milling and activation of lithium slag, which has application value, it does not obtain analcime materials with more stable structure through lithium slag, and does not study the yield of analcime.
[0004] In view of this, it is necessary to provide analcime activated by organic acid ball milling and a preparation method and application thereof, so as to solve or at least alleviate the technical problem of how to prepare analcime from lithium slag. Summary of the invention
[0005] The main purpose of the present invention is to provide analcime activated by organic acid ball milling and a preparation method and application thereof, aiming to solve the above-mentioned technical problem of how to prepare analcime from lithium slag.
[0006] To achieve the above object, the present invention provides a method for preparing analcime based on organic acid ball milling activation, comprising the steps of:
[0007] S1, providing lithium slag and mixed acid; the lithium slag contains Li, Si, Al, Na, K, F and Ca; the mixed acid includes a first organic acid and a second organic acid, the first organic acid includes citric acid, the second organic acid includes oxalic acid, and the mass ratio of the first organic acid to the second organic acid is 0.8-3:1;
[0008] S2, using the lithium slag and the mixed acid as solid materials, and ball-milling the solid materials and water to obtain a ball-milled product; the mass ratio of the mixed acid to the lithium slag is 1.5-5:5; the mass percentage of the water to the solid materials is 20-60%; the rotation speed of the ball mill is 290-310 r / min or 450-800 r / min, and the ball milling time is not less than 120 min;
[0009] S3, mixing the ball milling product and an alkaline solution to obtain a liquid to be treated; subjecting the liquid to be treated to a hydrothermal treatment to obtain a reaction liquid; the alkaline solution contains an alkaline substance, and the alkaline substance includes one or more of sodium hydroxide and potassium hydroxide; the temperature of the hydrothermal treatment is 130-210° C., and the duration of the hydrothermal treatment is 40-180 min;
[0010] S4, performing solid-liquid separation on the reaction liquid to obtain a solid separation; the solid separation contains analcime.
[0011] Furthermore, the first organic acid is citric acid, the second organic acid is oxalic acid, the mass ratio of the first organic acid to the second organic acid is 0.8-2:1; the mass ratio of the mixed acid to the lithium slag is 1.5-3.5:5.
[0012] Furthermore, the rotation speed of the ball mill is 500-560r / min, the duration of the ball mill is 120-300min, and the ball-to-material mass ratio used in the ball mill is 4-12:1.
[0013] Furthermore, the concentration of the alkaline substance in the alkaline solution is 0.5-4 mol / L.
[0014] Furthermore, the mass volume ratio of the ball-milled product to the alkaline solution is 0.5-10 g:45 mL.
[0015] Furthermore, the hydrothermal treatment is carried out by microwave hydrothermal treatment; and the microwave hydrothermal treatment is carried out in a microwave hydrothermal reactor.
[0016] Further, the mass proportion of the Li element in the lithium slag is 0.1-2%, the mass proportion of the Si element in the lithium slag is 10-15%, the mass proportion of the Al element in the lithium slag is 5-12%, the mass proportion of the Na element in the lithium slag is 5-10%, the mass proportion of the K element in the lithium slag is 5-10%, the mass proportion of the F element in the lithium slag is 2-8%, and the mass proportion of the Ca element in the lithium slag is 5-10%;
[0017] The lithium slag contains nepheline, muscovite and orthoclase; the lithium slag has a framework aluminosilicate structure.
[0018] The present invention also provides analcime, comprising: preparing the analcime by any of the above-mentioned analcime preparation methods.
[0019] The present invention also provides a use of any of the above-mentioned analcime in arsenic removal or sulfur-resistant arsenic removal.
[0020] The present invention also provides an arsenic removal method, comprising: using any of the above-mentioned analcime to adsorb arsenic in arsenic-containing flue gas, the adsorption is carried out at a temperature of 400-900°C, and the adsorption time is 20-90 minutes; the arsenic-containing flue gas contains As2O3, or the arsenic-containing flue gas contains As2O3 and SO2;
[0021] When the arsenic-containing flue gas contains As2O3, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L; when the arsenic-containing flue gas contains As2O3 and SO2, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L, and the volume proportion of SO2 in the arsenic-containing flue gas is not higher than 15%.
[0022] Compared with the prior art, the present invention has at least the following advantages:
[0023] The present invention is based on citric acid and oxalic acid. After ball milling lithium slag at a certain humidity, a ball milling product is obtained, and then hydrothermal synthesis is performed in a specific alkaline solution to obtain analcime products with high crystallinity and high yield; and the analcime in the present invention can still effectively resist sulfur and remove arsenic at a high temperature of 800°C, and has a stable structure. In this way, the present invention utilizes the slag extracted from lithium leaching as a resource, provides a new way for lithium slag disposal, and realizes the transformation of waste into treasure; the preparation method of analcime provided by the present invention is suitable for large-scale preparation by enterprises and conforms to production practice.
[0024] In the process of ball milling, the hydrogen ions in the organic acid are used to attack the aluminum silicate skeleton during ball milling; at the same time, citric acid and oxalic acid synergistically attack Si-O and Al-O bonds, promote the release of silicon and aluminum elements, and enhance the reaction activity of lithium slag for subsequent hydrothermal synthesis; in the process of hydrothermal synthesis, citric acid does not preferentially adsorb calcium ions because it complexes with many divalent metal ions, while after adding oxalic acid, oxalic acid preferentially adsorbs Ca ions. 2+ Complexation, resulting in Ca 2+ The lower concentration can further inhibit the volcanic ash reaction and improve the crystallinity and yield of analcime. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0026] Figure 1 The XRD diagram of the lithium slag in the analysis example 1 of the present invention;
[0027] Figure 2 The activity index diagram of lithium slag after ball milling at different ball milling speeds in Example 1 of the present invention;
[0028] Figure 3 This is a graph of the activity index of lithium slag after ball milling at different ball milling times in Example 2 of the present invention;
[0029] Figure 4 The activity index diagram of lithium slag after ball milling at different ball-to-material ratios in Example 3 of the present invention;
[0030] Figure 5 This is a graph of the activity index of lithium slag after ball milling under different auxiliary materials (different ball milling auxiliary materials) in Example 4 of the present invention;
[0031] Figure 6 The activity index diagram of lithium slag after ball milling under different mixed acid ratios (mass ratio of citric acid and oxalic acid) in Example 5 of the present invention;
[0032] Figure 7 The graph of the activity index of lithium slag after ball milling under different auxiliary material ratios (mass ratio of auxiliary material to main material lithium slag) in Example 6 of the present invention;
[0033] Figure 8 : is the XRD diagram of the product (analcite) prepared in Example 7 of the present invention; in the figure, citric acid + oxalic acid refers to the product prepared in Example 7;
[0034] Fig. 9 This is a diagram showing the effect of the adsorbent adsorbing gaseous arsenic at different adsorption temperatures in Example 8 of the present invention;
[0035] Fig.10 This is a diagram showing the effect of the adsorbent on adsorbing gaseous arsenic at different sulfur dioxide concentrations in Example 9 of the present invention;
[0036] Fig.11 This is the XRD pattern of the product prepared in Comparative Example 1 of the present invention;
[0037] Fig.12 This is the XRD diagram of the product prepared in Comparative Example 2 of the present invention;
[0038] Fig.13This is the XRD diagram of the product prepared in Comparative Example 3 of the present invention;
[0039] Fig.14 This is the XRD diagram of the product prepared in Comparative Example 4 of the present invention;
[0040] Fig.15 This is the XRD diagram of the product prepared in Comparative Example 5 of the present invention.
[0041] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0044] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any methods, equipment and materials of the prior art similar or equivalent to the methods, equipment and materials described in the embodiments of the present invention can also be used to implement the present invention.
[0045] In the present invention, when calculating the ball-to-material ratio, lithium slag, alkaline auxiliary materials and water are all counted as materials for ball milling. In the embodiments and comparative examples of the present invention, alumina grinding balls are used for ball milling, and the number ratio of alumina grinding balls is large balls (diameter 15mm): medium balls (diameter 10mm): small balls (diameter 5mm) = 15:9:6; in the present invention, further, the number ratio of grinding balls can be large balls (diameter 14-16mm): medium balls (diameter 9-11mm): small balls (diameter 4-6mm) = 14-16:8-10:5-7. The microwave hydrothermal reactor used in the embodiments and comparative examples of the present invention comes from Beijing Xianghu Technology Development Co., Ltd., which is a multifunctional microwave hydrothermal parallel synthesizer, model XH-800SP, and microwave frequency 2450MHz.
[0046] In the present invention, the calculation formula of the activity index of lithium slag after ball milling is: Among them, α represents the activity index of lithium slag after ball milling, m1 represents the active aluminum content in lithium slag after ball milling, and m0 represents the active aluminum content in lithium slag before ball milling.
[0047] In the present invention, the aluminum that can be dissolved after alkali leaching is defined as active aluminum; wherein the alkali leaching steps are as follows:
[0048] Prepare 100mL of 1mol / L sodium hydroxide solution, and pour the solution into a 250mL beaker; place the beaker on a digital constant temperature magnetic stirrer and heat it to 60°C; add 3g of the object to be tested (lithium slag after ball milling or lithium slag before ball milling) into the beaker, and conduct an alkaline leaching experiment with a leaching time of 30min and a stirring speed of 300r / min; after the leaching is completed, filter while hot, acidify the filtrate with concentrated HNO3 to pH <2, and place it in a refrigerator for testing, and then use ICP-OES to analyze and test the aluminum concentration. The higher the active aluminum content, the greater the activity of the lithium slag.
[0049] The present invention provides a method for preparing analcime based on organic acid ball milling activation, comprising the steps of:
[0050] S1, providing lithium slag and mixed acid; the lithium slag contains Li element, Si element, Al element, Na element, K element, F element, and Ca element; the mixed acid includes a first organic acid and a second organic acid, the first organic acid includes citric acid, the second organic acid includes oxalic acid, and the mass ratio of the first organic acid to the second organic acid is 0.8-3:1; preferably, the first organic acid is citric acid, the second organic acid is oxalic acid, and the mass ratio of the first organic acid to the second organic acid is 0.8-2:1.
[0051] In the present invention, the mass proportion of the Li element in the lithium slag is 0.1-2%, the mass proportion of the Si element in the lithium slag is 10-15%, the mass proportion of the Al element in the lithium slag is 5-12%, the mass proportion of the Na element in the lithium slag is 5-10%, the mass proportion of the K element in the lithium slag is 5-10%, the mass proportion of the F element in the lithium slag is 2-8%, and the mass proportion of the Ca element in the lithium slag is 5-10%.
[0052] The lithium slag contains the physical phases of nepheline, muscovite and orthoclase; the lithium slag has aluminosilicate, especially a framework aluminosilicate structure.
[0053] S2, using the lithium slag and the mixed acid as solid materials, and ball-milling the solid materials and water to obtain a ball-milled product.
[0054] The present invention can promote the release of silicon and aluminum elements in lithium slag, increase the amorphization degree of lithium slag, enhance the reaction activity of lithium slag, and is easy to operate by performing the ball milling.
[0055] In the present invention, the mass ratio of the mixed acid to the lithium slag is 1.5-5:5; the mass percentage of the water to the solid material is 20-60%; the rotation speed of the ball mill is 290-310 r / min or 450-800 r / min, and the ball milling time is not less than 120 min.
[0056] Preferably, the mass ratio of the mixed acid and the lithium slag is 1.5-3.5:5 or 1.9-2.1:5; the mass percentage of the water and the solid material is 30-50%; the rotation speed of the ball mill is 500-560r / min; the ball milling time is 120-300min or 120-250min; in the present invention, the ball-to-material mass ratio used in the ball mill is 4-12:1, and further 7-9:1.
[0057] When the ball milling is performed, the present invention performs forward rotation and reverse rotation in sequence; there is an interval between the forward rotation and the reverse rotation, and between the reverse rotation and the forward rotation; wherein, the set time of each forward rotation is 5-15 minutes (specifically 10 minutes), the set time of each reverse rotation is 5-15 minutes (specifically 10 minutes), and the interval time is set to 3-7 minutes (specifically 5 minutes); when the ball milling time reaches the set time, the ball milling is stopped, and the interval time is included in the ball milling time.
[0058] S3, mixing the ball-milled product and an alkaline solution to obtain a liquid to be treated; and subjecting the liquid to be treated to a hydrothermal treatment (hydrothermal reaction) to obtain a reaction liquid.
[0059] In the present invention, the alkaline solution contains an alkaline substance, and the alkaline substance includes one or more of sodium hydroxide and potassium hydroxide; the concentration of the alkaline substance in the alkaline solution is 0.5-4 mol / L, further 0.7-1.3 mol / L or 0.9-1.1 mol / L. The mass volume ratio of the ball milling product to the alkaline solution is 0.5-10 g:45 mL, further 1-5 g:45 mL.
[0060] The temperature of the hydrothermal treatment in the present invention is 130-210°C, further 140-160°C; the duration of the hydrothermal treatment is 40-180min, further 110-130min; the hydrothermal treatment is carried out by microwave hydrothermal treatment; the microwave hydrothermal treatment is carried out in a microwave hydrothermal reactor; by adopting the microwave hydrothermal treatment, microwave field energy can be applied to the material in the reactor during the synthesis stage, so that the crystallization rate of the zeolite is accelerated.
[0061] S4, performing solid-liquid separation on the reaction liquid to obtain a solid separation (separation residue); the solid separation contains analcime.
[0062] The analcime preparation method provided in the present invention is simple and low-cost, and the prepared analcime has a large adsorption capacity, which can not only obtain analcime products, but also effectively reduce the emission of gaseous arsenic in non-ferrous smelting enterprises under high temperature environment, and reduce the stockpiling of lithium slag in the lithium carbonate industry, thereby realizing resource utilization.
[0063] As a new type of three-dimensional material, analcime is widely used in the fields of environment, medicine and catalysis. Its main component is consistent with lithium slag, so lithium slag has the potential to synthesize analcime. The present invention uses lithium slag as a raw material to synthesize zeolite, which adsorbs gaseous arsenic in flue gas. On the one hand, it solves the problem of difficulty in recycling lithium slag resources, and on the other hand, it provides a simple and low-cost method for efficiently treating gaseous arsenic.
[0064] The technical key of the present invention mainly lies in:
[0065] First, under the joint action of the first organic acid (citric acid) and the second organic acid (oxalic acid), the lithium slag is activated through mechanical ball milling to enhance its activity; mechanical ball milling utilizes the rotation of the drum to cause the grinding balls and materials to continuously collide, shear and rub in the tank body, thereby achieving the effect of material crushing, mixing and enhancing surface activity.
[0066] During the ball milling process, the hydrogen ions in the auxiliary organic acid are used to attack the aluminosilicate skeleton during ball milling; the auxiliary organic acid anions are adsorbed on the cationic reaction sites in the mineral crystals, and the cations in the lattice are dissolved through polarization, causing the mineral crystal structure to be destroyed; at the same time, citric acid and oxalic acid synergistically attack the Si-O and Al-O bonds, promote the release of silicon and aluminum elements, and enhance the reaction activity of lithium slag to facilitate subsequent hydrothermal synthesis; and in the ball milling process, the auxiliary material can also be used as a grinding aid.
[0067] Secondly, after mixed acid ball milling, the activated lithium slag is subjected to hydrothermal synthesis. Although the lithium slag and citric acid are co-milled and then hydrothermally synthesized, analcime with a certain crystallinity and yield can be obtained. However, during the hydrothermal synthesis, citric acid complexes with many divalent metal ions and does not preferentially adsorb calcium ions. After adding oxalic acid, oxalic acid preferentially adsorbs Ca ions. 2+ Complexation, resulting in Ca 2+ The concentration is low, thereby inhibiting the volcanic ash reaction and further improving the crystallinity and yield of zeolite; the lithium slag after ball milling activation is dissolved, diffused, monomer reconstructed, and condensed in a microwave hydrothermal environment to form zeolite.
[0068] Thirdly, the present invention has specific requirements for the humidity during the ball milling process, mainly because appropriate moisture can cooperate with organic acid to destroy the lithium slag structure, thereby promoting the release of Si and Al elements.
[0069] Fourthly, the present invention has specific requirements for the alkaline solution used in hydrothermal treatment, mainly because OH - The concentration will affect the dissolution rate of silicon and aluminum and the crystallization rate of zeolite, so an appropriate concentration should be used; and the introduction of Ca 2+ Mg 2+ It will promote volcanic ash reaction and thus inhibit the formation of analcime.
[0070] Fifth, the present invention can utilize the F element in lithium slag in situ to play the role of inorganic template during hydrothermal treatment and at the same time 2+ Combined with the formation of CaF2 precipitation, it inhibits the volcanic ash reaction and promotes the formation of analcime.
[0071] The present invention also provides analcime, comprising: preparing the analcime by any of the above-mentioned analcime preparation methods.
[0072] The present invention also provides a use of any of the above-mentioned analcime in arsenic removal or sulfur-resistant arsenic removal.
[0073] As a specific embodiment of the above application, the present invention also provides an arsenic removal method, comprising: using any of the above-mentioned analcime to adsorb arsenic in arsenic-containing flue gas, the adsorption is carried out at a temperature of 400-900°C (preferably 750-850°C or 750-800°C), and the adsorption time is 20-90min (preferably 25-35min); the arsenic-containing flue gas contains As2O3, or the arsenic-containing flue gas contains As2O3 and SO2.
[0074] When the arsenic-containing flue gas contains As2O3, other components in the arsenic-containing flue gas may include or be oxygen, argon, and carbon dioxide, and the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L (preferably 0.5-0.8 mg / L); when the arsenic-containing flue gas contains As2O3 and SO2, other components in the arsenic-containing flue gas may include or be oxygen, argon, and carbon dioxide, and the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L (preferably 0.5-0.8 mg / L), and the volume proportion of SO2 in the arsenic-containing flue gas is not higher than 15% (preferably 4-6% or 5-10%).
[0075] The following are specific examples of the present invention:
[0076] Analysis example 1
[0077] Take the lithium slag stored in a lithium carbonate production company in Jiangxi.
[0078] 1. In this analysis example, the element composition of lithium slag is shown in Table 1. In Table 1, Rb* and Cs* are tested by digestion-ICP, and the remaining elements are tested by XRF.
[0079] Table 1 Element composition of lithium slag (mass %)
[0080]
[0081] 2. In this analysis, lithium slag contains nepheline, muscovite and orthoclase. For XRD analysis of lithium slag, see Figure 1 As shown; after analysis, the lithium slag has a framework aluminosilicate structure.
[0082] Example 1
[0083] Take the lithium slag in Analysis Example 1 and ball mill them at ball mill speeds of 300, 350, 400, 450, 500, 550, 600, 650, and 700 r / min, respectively, to obtain ball milling products at different ball milling speeds; the ball-to-material ratio used in the ball milling is 6:1, and the ball milling time is 25 min (the ball mill is set to rotate forward for 10 min, interval 5 min, and reverse for 10 min).
[0084] The activity index of the ball-milled product (lithium slag after ball-milling) at different ball-milling speeds was tested; Figure 2 As shown, when the ball milling speed is 550r / min, the activity index of the lithium slag after ball milling reaches 9.1.
[0085] Example 2
[0086] Take the lithium slag in Analysis Example 1, and ball mill them respectively under the conditions of ball milling time of 25, 50, 75, 100, 125, 150, 200, and 250 min (set the ball mill to rotate forward for 10 min, interval 5 min, reverse for 10 min, interval 5 min), and obtain the ball milling products under different ball milling times; the ball-to-material ratio used in the ball milling is 6:1, and the ball milling speed is 550 r / min.
[0087] The activity index of the ball-milled products (lithium slag after ball-milling) at different ball-milling times was tested; Figure 3 As shown in the figure, when the ball milling time reaches 125 min, the activity index of lithium slag after ball milling basically no longer increases, and the activity index reaches 15.2 at this time.
[0088] Example 3
[0089] Take the lithium slag in Analysis Example 1 and ball mill them under the conditions of ball to material ratio of 4:1, 6:1, 8:1 and 10:1 respectively to obtain ball milling products under different ball to material ratios; the ball milling time used is 125min (the ball mill is set to rotate forward for 10min, interval of 5min, reverse for 10min, interval of 5min), and the ball milling speed is 550r / min.
[0090] The activity index of the ball milling product (lithium slag after ball milling) under different ball-to-material ratios was tested; Figure 4 As shown in the figure, when the ball-to-material ratio is 8:1, the activity index of the lithium slag after ball milling reaches 20; when the ball-to-material ratio is 10:1, the activity index of the lithium slag after ball milling decreases rapidly. It is speculated that there may be too little material, causing part of the lithium slag to adhere to the ball mill and the grinding balls, resulting in systematic errors and making the measured value smaller.
[0091] Example 4
[0092] Take the lithium slag in the analysis example 1, match the auxiliary material and the lithium slag in a mass ratio of 3:5 as a solid material, and ball-mill the solid material and water together to obtain ball-milled products with different auxiliary materials; in this embodiment, ball milling is performed under the condition that the auxiliary materials are sodium hydroxide, citric acid, oxalic acid, sodium citrate, and mixed acid (citric acid and oxalic acid are matched in a mass ratio of 1:1). When ball milling is performed in this embodiment, the mass percentage of water and solid material is 40% (equivalent to the water content), the ball-to-material ratio used in ball milling is 8:1, the ball milling time is 125min (the ball mill is set to rotate forward for 10min, with an interval of 5min, and reverse for 10min, with an interval of 5min), and the ball milling speed is 550r / min.
[0093] The activity index of the ball-milled products (lithium slag after ball-milling) with different auxiliary materials was tested; Figure 5 As shown in the figure, the activity index of the lithium slag after ball milling corresponding to the mixed acid reached 34.8. It is speculated that citric acid and oxalic acid have preferential orientation for the dissolution of Si and Al, which makes citric acid and oxalic acid synergistically attack Si-O bonds and Al-O bonds under the action of mixed acid, destroying the aluminosilicate skeleton of the mineral; on the other hand, the organic acid anions are adsorbed on the cationic reaction sites in the mineral crystals, and the cations in the lattice are dissolved through polarization, causing the mineral crystal structure to be destroyed.
[0094] Example 5
[0095] Take the lithium slag in the analysis example 1, mix citric acid and oxalic acid in the mass ratio of 1:3, 1:2, 1:1, 2:1, 3:1 to form mixed acids of different proportions, and mix the mixed acids of each ratio with the lithium slag in the mass ratio of 3:5 as solid materials, and then respectively ball-mill each solid material with water to obtain ball-milled products under different mixed acid ratios. In this embodiment, when ball milling, the mass percentage of water and solid material is 40% (equivalent to the water content), the ball-to-material ratio used in ball milling is 8:1, the ball milling time is 125min (the ball mill is set to rotate forward for 10min, interval 5min, reverse for 10min, interval 5min), and the ball milling speed is 550r / min.
[0096] The activity index of the ball-milled products (lithium slag after ball-milling) at different mixed acid ratios was tested; Figure 6 It can be seen that when the mass ratio of citric acid to oxalic acid is 1:1, the activity index of lithium slag after ball milling reaches 34.8. This is because under the action of mixed acid, citric acid and oxalic acid can synergistically attack Si-O bonds and Al-O bonds and destroy the aluminosilicate skeleton of the mineral.
[0097] Example 6
[0098] Take the lithium slag in the analysis example 1, mix citric acid and oxalic acid in a mass ratio of 1:1 to form a mixed acid, mix the mixed acid and lithium slag in a mass ratio of 0, 1:5, 2:5, 3:5, 4:5, 1:1 to form solid materials of different proportions (equivalent to different auxiliary material ratios, a mass ratio of 0 represents no mixed acid), and then respectively ball-mill each solid material and water to obtain ball-milled products under different auxiliary material ratios. In this embodiment, when ball milling, the mass percentage of water and solid material is 40% (equivalent to water content), the ball-to-material ratio used in ball milling is 8:1, the ball milling time is 125min (the ball mill is set to rotate forward for 10min, with an interval of 5min, and reverse for 10min, with an interval of 5min), and the ball milling speed is 550r / min.
[0099] The activity index of the ball-milled product (lithium slag after ball-milling) with different auxiliary material ratios was tested; Figure 7 It can be seen that when mixed acid is used as an auxiliary material, the optimal auxiliary material ratio is 2:5, and the activity index of lithium slag after ball milling reaches 38.1. The synergistic destructive effect of mixed acid on the aluminosilicate skeleton effectively reduces the amount of auxiliary materials used.
[0100] Example 7
[0101] Take the lithium slag in the analysis example 1, mix citric acid and oxalic acid in a mass ratio of 1:1 to form a mixed acid, mix the mixed acid and lithium slag in a mass ratio of 2:5 to form a solid material, and then ball-mill each solid material and water to obtain a ball-milled product (lithium slag after ball milling). In this embodiment, when ball milling, the amount of lithium slag is 7.8g, the mass percentage of water and solid material is 40% (equivalent to the water content), the ball-to-material ratio used in ball milling is 8:1, the ball milling time is 125min (the ball mill is set to rotate forward for 10min, with an interval of 5min, and reverse for 10min, with an interval of 5min), and the ball milling speed is 550r / min.
[0102] Weigh 3 g of the ball-milled product into a microwave hydrothermal reactor, add 45 mL of 1 mol / L NaOH solution and carry out hydrothermal reaction (microwave hydrothermal reaction). The temperature of the hydrothermal reaction is 150° C., the time of the hydrothermal reaction is 120 min, and the reaction liquid is obtained after the hydrothermal reaction is completed.
[0103] The reaction solution was centrifuged at a speed of 8000 r / min for 10 min at room temperature, and vacuum filtered to achieve solid-liquid separation to obtain a separation liquid and separation residue; the separation residue was dried to obtain the prepared product.
[0104] The prepared product was measured by XRD to confirm whether it was analcime. The crystallinity of the prepared product was calculated using jade software. The aluminum content in the separation liquid was measured by ICP, and the analcime yield was calculated by the proportion of aluminum consumed in the reaction in the total aluminum (aluminum in the lithium slag). The aluminum in the separation liquid was defined as unconsumed aluminum, and the aluminum entering the separation slag was defined as aluminum consumed in the reaction.
[0105] like Figure 8 As shown, the prepared product in this example is analcime; the crystallinity is 54.9%; and the analcime yield is 47.7%.
[0106] Example 8
[0107] 0.1 g of the prepared product (analcime) in Example 7 was taken as an adsorbent, and the adsorbent was placed in a gaseous arsenic adsorption system to carry out an arsenic adsorption experiment, and the adsorption time was 30 min.
[0108] In this embodiment, the gaseous arsenic adsorption system is composed of an arsenic hydrogen generator, an adsorption reactor, and an exhaust gas treatment system. The arsenic hydrogen generator produces arsenic hydrogen, which enters the adsorption reactor together with the simulated flue gas; the adsorption reactor is composed of a two-stage reactor, arsenic hydrogen enters the first stage reactor to be oxidized into arsenic trioxide, arsenic trioxide enters the second stage reactor for adsorption reaction, and the exhaust gas is discharged through the exhaust gas treatment system.
[0109] In this embodiment, the atmosphere used for the simulated flue gas is O2 5%, Ar 87%, SO2 5%, CO2 3% by volume, and the flue gas flow rate is 400 mL / min; the concentration of As2O3 in the simulated flue gas is 0.6 mg / L.
[0110] In this embodiment, the above arsenic adsorption experiments were carried out at adsorption temperatures of 400, 500, 600, 700, and 800°C, respectively.
[0111] See also Fig. 9 As shown, the prepared product (analcime) in Example 7 can adsorb gaseous arsenic (referring to As2O3) in an amount of 22.26 mg / g at an adsorption temperature of 800°C, and has excellent gaseous arsenic adsorption capacity.
[0112] Example 9
[0113] 0.1 g of the prepared product (analcime) in Example 7 was taken as an adsorbent, and the adsorbent was placed in a gaseous arsenic adsorption system to carry out an arsenic adsorption experiment. The adsorption temperature was 400° C. and the adsorption time was 30 min.
[0114] In this embodiment, the gaseous arsenic adsorption system is composed of an arsenic hydrogen generator, an adsorption reactor, and an exhaust gas treatment system. The arsenic hydrogen generator produces arsenic hydrogen, which enters the adsorption reactor together with the simulated flue gas. The adsorption reactor is composed of a two-stage reactor. Arsenic hydrogen enters the first stage reactor to be oxidized to arsenic trioxide, and arsenic trioxide enters the second stage reactor for adsorption reaction, and the exhaust gas is discharged through the exhaust gas treatment system.
[0115] In this embodiment, the above arsenic adsorption experiment is carried out on different simulated flue gases; the compositions of the simulated flue gases are respectively:
[0116] In terms of volume percentage, the atmosphere used for the simulated flue gas (corresponding to 0%) is O2 5%, Ar 92%, SO20%, CO23%, and the flue gas flow rate is 400mL / min; the concentration of As2O3 in the simulated flue gas is 0.6mg / L.
[0117] In terms of volume percentage, the atmosphere used for the simulated flue gas (corresponding to 5%) is O2 5%, Ar 87%, SO25%, CO23%, and the flue gas flow rate is 400mL / min; the concentration of As2O3 in the simulated flue gas is 0.6mg / L.
[0118] In terms of volume percentage, the atmosphere used for the simulated flue gas (corresponding to 10%) is O2 5%, Ar 82%, SO2 10%, CO2 3%, and the flue gas flow rate is 400mL / min; the concentration of As2O3 in the simulated flue gas is 0.6mg / L.
[0119] See also Fig.10 As shown, when the SO2 concentration is 5%, the gaseous arsenic (referring to As2O3) adsorption capacity of the product (analcime) prepared in Example 7 can reach 16.63 mg / g, which has excellent gaseous arsenic adsorption capacity.
[0120] Comparative Example 1
[0121] 1. Obtaining the prepared product:
[0122] When obtaining the prepared product, compared with Example 7, the mixed acid in the solid material in this comparative example was adjusted to citric acid, and other conditions remained unchanged.
[0123] In this comparative example, see Fig.11 As shown, the prepared product is analcime with a crystallinity of 47.1% and analcime yield of 42.5%.
[0124] 2. Arsenic adsorption experiment:
[0125] When conducting the arsenic adsorption experiment, compared with Example 8, the adsorbent in this comparative example was adjusted to the prepared product in this comparative example, and the adsorption temperature was limited to 800° C., while other conditions remained unchanged.
[0126] In this comparative example, the adsorption amount of gaseous arsenic (referred to as As2O3) by the adsorbent is 20.7 mg / g.
[0127] Comparative Example 2
[0128] 1. Obtaining the prepared product:
[0129] When obtaining the prepared product, compared with Example 7, the mixed acid in the solid material in this comparative example was adjusted to oxalic acid, and other conditions remained unchanged.
[0130] In this comparative example, see Fig.12 As shown, the prepared product is analcime with a crystallinity of 31.4% and analcime yield of 29.6%.
[0131] 2. Arsenic adsorption experiment:
[0132] When conducting the arsenic adsorption experiment, compared with Example 8, the adsorbent in this comparative example was adjusted to the prepared product in this comparative example, and the adsorption temperature was limited to 800° C., while other conditions remained unchanged.
[0133] In this comparative example, the adsorption amount of gaseous arsenic (referred to as As2O3) by the adsorbent is 15.8 mg / g.
[0134] Comparative Example 3
[0135] 1. Obtaining the prepared product:
[0136] When obtaining the prepared product, compared with Example 7, the oxalic acid in the mixed acid was adjusted to hydrochloric acid (citric acid was retained in the mixed acid, and the proportion remained unchanged), and other conditions remained unchanged.
[0137] In this comparative example, see Fig.13 As shown, no analcime was generated in the product.
[0138] 2. Arsenic adsorption experiment:
[0139] When conducting the arsenic adsorption experiment, compared with Example 8, the adsorbent in this comparative example was adjusted to the prepared product in this comparative example, and the adsorption temperature was limited to 800° C., while other conditions remained unchanged.
[0140] In this comparative example, the adsorption amount of gaseous arsenic (referred to as As2O3) by the adsorbent is 4.3 mg / g.
[0141] Comparative Example 4
[0142] 1. Obtaining the prepared product:
[0143] When obtaining the prepared product, compared with Example 7, the alkaline solution used in the hydrothermal process of this comparative example was adjusted to pure water, and other conditions remained unchanged.
[0144] In this comparative example, see Fig.14 As shown, analcime was generated in the prepared product, but the crystallinity was only 12.5%, and the analcime yield was 10.7%.
[0145] 2. Arsenic adsorption experiment:
[0146] When conducting the arsenic adsorption experiment, compared with Example 8, the adsorbent in this comparative example was adjusted to the prepared product in this comparative example, and the adsorption temperature was limited to 800° C., while other conditions remained unchanged.
[0147] In this comparative example, the adsorption amount of gaseous arsenic (referred to as As2O3) by the adsorbent is 8.9 mg / g.
[0148] Comparative Example 5
[0149] 1. Obtaining the prepared product:
[0150] When obtaining the prepared product, compared with Example 7, the lithium slag in this comparative example is directly ball-milled (without adding mixed acid and water), and other conditions remain unchanged.
[0151] In this comparative example, see Fig.15 As shown, analcime was generated in the prepared product, but the crystallinity was only 13.1% and the yield was 8.1%.
[0152] 2. Arsenic adsorption experiment:
[0153] When conducting the arsenic adsorption experiment, compared with Example 8, the adsorbent in this comparative example was adjusted to the prepared product in this comparative example, and the adsorption temperature was limited to 800° C., while other conditions remained unchanged.
[0154] In this comparative example, the adsorption amount of gaseous arsenic (referred to as As2O3) by the adsorbent is 13.69 mg / g.
[0155] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing analcime based on organic acid ball milling activation, characterized in that: Includes steps: S1, providing lithium slag and mixed acid; the lithium slag contains Li, Si, Al, Na, K, F and Ca; the mixed acid includes a first organic acid and a second organic acid, the first organic acid includes citric acid, the second organic acid includes oxalic acid, and the mass ratio of the first organic acid to the second organic acid is 0.8-3:1; S2, using the lithium slag and the mixed acid as solid materials, and ball-milling the solid materials and water to obtain a ball-milled product; the mass ratio of the mixed acid to the lithium slag is 1.5-5:5; the mass percentage of the water to the solid materials is 20-60%; the rotation speed of the ball mill is 290-310 r / min or 450-800 r / min, and the ball milling time is not less than 120 min; S3, mixing the ball-milled product and an alkaline solution to obtain a liquid to be treated; and subjecting the liquid to be treated to a hydrothermal treatment to obtain a reaction liquid; The alkaline solution contains an alkaline substance, and the alkaline substance includes one or more of sodium hydroxide and potassium hydroxide; the temperature of the hydrothermal treatment is 130-210° C., and the duration of the hydrothermal treatment is 40-180 min; S4, performing solid-liquid separation on the reaction liquid to obtain a solid separation; the solid separation contains analcime.
2. The method for preparing analcime according to claim 1, characterized in that: The first organic acid is citric acid, the second organic acid is oxalic acid, the mass ratio of the first organic acid to the second organic acid is 0.8-2:1; the mass ratio of the mixed acid to the lithium slag is 1.5-3.5:
5.
3. The method for preparing analcime according to claim 1, characterized in that: The rotation speed of the ball mill is 500-560r / min, the duration of the ball mill is 120-300min, and the ball-to-material mass ratio used in the ball mill is 4-12:
1.
4. The method for preparing analcime according to claim 1, characterized in that: The concentration of the alkaline substance in the alkaline solution is 0.5-4 mol / L.
5. The method for preparing analcime according to claim 1, characterized in that: The mass volume ratio of the ball-milled product to the alkaline solution is 0.5-10 g:45 mL.
6. The method for preparing analcime according to claim 1, characterized in that: The hydrothermal treatment is carried out in a microwave hydrothermal reactor.
7. The method for preparing analcime according to claim 1, characterized in that: The mass proportion of the Li element in the lithium slag is 0.1-2%, the mass proportion of the Si element in the lithium slag is 10-15%, the mass proportion of the Al element in the lithium slag is 5-12%, the mass proportion of the Na element in the lithium slag is 5-10%, the mass proportion of the K element in the lithium slag is 5-10%, the mass proportion of the F element in the lithium slag is 2-8%, and the mass proportion of the Ca element in the lithium slag is 5-10%; The lithium slag contains nepheline, muscovite and orthoclase; the lithium slag has a framework aluminosilicate structure.
8. Analcime, characterized in that: include: The analcime is prepared by the method for preparing analcime according to any one of claims 1 to 7.
9. Use of the analcime as claimed in claim 8 in arsenic removal or sulfur-resistant arsenic removal.
10. A method for removing arsenic, characterized in that: include: The arsenic in the arsenic-containing flue gas is adsorbed by the analcime as claimed in claim 8, wherein the adsorption is performed at a temperature of 400-900° C. and the adsorption time is 20-90 minutes; the arsenic-containing flue gas contains As2O3, or the arsenic-containing flue gas contains As2O3 and SO2; When the arsenic-containing flue gas contains As2O3, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L; when the arsenic-containing flue gas contains As2O3 and SO2, the concentration of As2O3 in the arsenic-containing flue gas is not higher than 1 mg / L, and the volume proportion of SO2 in the arsenic-containing flue gas is not higher than 15%.
Citation Information
Patent Citations
Method for treating by-products
CN115710001A
Method for preparing analcime from silicon-aluminum tailings
CN115818659A
Sulfur-resistant and high-temperature-resistant gaseous arsenic adsorption material as well as preparation method and application thereof
CN117643861A
Zeolite and preparation method therefor
US20220033269A1